Quality management in surgery: improving clinical and surgical outcomes - FERREIRA,RAPHAELLA PAULA (2020)
ABSTRACT Quality is a term used by various specialists, from different perspectives, having as a common point to identify focuses that promote their development in institutional management. Quality processes allow us to improve assistance, reducing complication and death rates and reducing costs. Currently, the positive experience of the patient is highly valued and should be sought by all institutions. The benefits of quality procedures are extensive. There is evidence of lower complication and mortality rates, cost reduction, uniformity of care, improved communication and opportunity for health education. There is a need for financial investment by the institutions, but they can be converted in the future. The idea that these are just bureaucratic steps must be fought because individualistic attitudes are no longer part of safe medicine. The success of a quality process requires interdisciplinarity, integration with quality offices for effective communication. The implementation of feasible attitudes should be sought, with a high adherence rate to seek patient satisfaction and safety. We will address historical aspects, the requirements for the implementation of a quality program, the concepts of indicators and the aspects that influence the quality in surgery, in addition to presenting benefits that such a program can offer to the surgeon and the institution.